CIRCULATING OVARIAN STEROIDS IN RELATION TO SUPEROVULATORY RESPONSE AND EMBRYO RECOVERY IN SAHIWAL COWS AND HEIFERS - SIDDIQUl, M U; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Relationship between concentrations of circulating ovarian steroids and superovulation (sov.) response andembryo recovery was studied in 12 Sahiwal cattle (6 cows; 6 heifers) treated with FSH·P and PGF2" given i.m. 48hr after first FSH injection. On day 7 of first Al, donors were flushed and recovered embryos/ova were graded.Blood plasma samples were analysed for estrogen and progesterone concentrations using RIA. Among 6 cows(Group A), only 3 (50%) responded to sov treatment with 17 CL (5.67/donor) and total 10 embryos were recovered.Mean recovery of total and viable embryos for responded donors and overall were found to be 3.33 and 1. 00 and1.67 and 0.50 embryos/flush, respectively. All heifers (Group B) responded to sov. treatment with 50 CL (8.33/donor) and total 37 embryos (18 VE; 16 DE, 2 UFO and 1 zona) were recovered. Mean recovery of total and viableembryos was found to be 6.17 and 3.00 embryos/flush, respectively. Heifers yielded comparatively higher numberof mean ovulations (8.33) and embryos, both total (6.17) and viable (3.00), than those of cows (3.17, 1.67 and0.50, respectively). No significant variation was found in plasma progesterone concentrations among both groupsat all sample collection stages. The mean concentrations of plasma estrogen varied significantly between groups.It was found to be significantly (t=3.293, p
Keywords: Ovarian steroids; Superovulation response; Embryo recovery; Cows